UTILIZATION OF SOLID WASTE LEATHER INDUSTRY AS RAW MATERIAL MAKING SOAP - Suci Perwitasari, Dyah (Jurnal Teknik Kimia, 2011)
With the increase in the development of technology, then today often products from a factorythat various forms in the market in order to satisfies the consumer. For example was the number of soapproducts that emerged. Because of that as the new alternative that is looking for the alternative base forthe production base of soap. The alternative that will be developed was the production of soap from thatis fat. This research was to make laundry detergent by making use of the waste of the skin industry. Wasbased on results of the analysis it was known the best condition was achieved at the time of the increase7 gram and the increase KOH 15 gram with the level of free alkali 0.094 %, fat not 1.80 %, and thenumber fatty acid 68.7 %. Meaning that at the moment the condition for the quality of laundry detergentbased on the Standard of Nasional Indonesia could be filled.Key words: solid waste , skin industry,KOH, fatty acid, soap.